Dopaminergic Presynaptic Modulation of Nigral Afferents: Its Role in the Generation of Recurrent Bursting in Substantia Nigra Pars Reticulata Neurons - Aceves, Jose D.; Rueda-Orozco, Pavel E.; Hernandez, Ricardo; Plata, Victor; Ibanez-Sandoval, Osvaldo; Galarraga, Elvira; Bargas, Jose (Frontiers in Systems Neuroscience, 2011)
Previous work has shown the functions associated with activation of dopamine presynaptic receptors in some substantia nigra pars reticulata (SNr) afferents: i) striatonigral terminals (direct pathway) posses presynaptic dopamine D1-class receptors whose action is to enhance inhibitory postsynaptic currents (IPSCs) and GABA transmission. ii) Subthalamonigral terminals posses D1- and D2-class receptors where D1-class receptor activation enhances and D2-class receptor activation decreases excitatory postsynaptic currents (EPSCs). Here we report that pallidonigral afferents posses D2-class receptors (D3 and D4 types) that decrease inhibitory synaptic transmission via presynaptic modulation. No action of D1-class agonists was found on pallidonigral synapses. In contrast, administration of D1-receptor antagonists greatly decreased striatonigral IPSCs in the same preparation, suggesting that tonic dopamine levels help in maintaining the function of the striatonigral (direct) pathway. When both D3 and D4 type receptors were blocked, pallidonigral IPSCs increased in amplitude while striatonigral connections had no significant change, suggesting that tonic dopamine levels are repressing a powerful inhibition conveyed by pallidonigral synapses (a branch of the indirect pathway). We then blocked both D1- and D2-class receptors to acutely decrease direct pathway (striatonigral) and enhance indirect pathways (subthalamonigral and pallidonigral) synaptic force. The result was that most SNr projection neurons entered a recurrent bursting firing mode similar to that observed during Parkinsonism in both patients and animal models. These results raise the question as to whether the lack of dopamine in basal ganglia output nuclei is enough to generate some pathological signs of Parkinsonism.